2022
DOI: 10.3390/ijms23116349
|View full text |Cite
|
Sign up to set email alerts
|

Impact of N-Terminal Tags on De Novo Vimentin Intermediate Filament Assembly

Abstract: Vimentin, a type III intermediate filament protein, is found in most cells along with microfilaments and microtubules. It has been shown that the head domain folds back to associate with the rod domain and this association is essential for filament assembly. The N-terminally tagged vimentin has been widely used to label the cytoskeleton in live cell imaging. Although there is previous evidence that EGFP tagged vimentin fails to form filaments but is able to integrate into a pre-existing network, no study has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 96 publications
1
9
0
Order By: Relevance
“…Although it is not clear how Liu and co-workers observed the effect of vimentin at individual cell level [4], it could be due to the tag used in their study. In this regard, we have recently shown that the N-terminally tagged vimentin only forms aggregates that align along intercellular junctions in an epithelial colony, and although the tagged vimentin integrates into the pre-existing network, the laments were found to be weaker [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is not clear how Liu and co-workers observed the effect of vimentin at individual cell level [4], it could be due to the tag used in their study. In this regard, we have recently shown that the N-terminally tagged vimentin only forms aggregates that align along intercellular junctions in an epithelial colony, and although the tagged vimentin integrates into the pre-existing network, the laments were found to be weaker [33].…”
Section: Discussionmentioning
confidence: 99%
“…The full-length human vimentin cDNA was sub-cloned in pLPChygro as described previously [33]. The constructs were named pLPChygro-FV (full-length vimentin) and pLPChygro-CV (control vector).…”
Section: Plasmid Constructs Cdna Cloning Retrovirus Production and Sp...mentioning
confidence: 99%
See 1 more Smart Citation
“…When 70–80% confluent, cells were washed twice with PBS and lysed using 250 μL/well Laemmli lysis buffer (2% sodium dodecyl sulphate (SDS), 20% glycerol, 125 mM Tris-HCl, pH 6.8). SDS gel electrophoresis and Western blotting were performed as described previously [ 55 ]. ECL prime detection reagent (Cat # PRN2232, GE Healthcare, Lisburn, UK) and ChemiDoc (BioRad, Watford, UK) were used to visualise protein bands.…”
Section: Methodsmentioning
confidence: 99%
“…The full-length human vimentin cDNA was sub-cloned into pLPChygro as described previously [ 55 ]. The constructs were named pLPChygro-FV (full-length vimentin) and pLPChygro-CV (control vector) .…”
Section: Methodsmentioning
confidence: 99%